Au@CuS Nanoshells for Surface-Enhanced Raman Scattering Image-Guided Tumor Photothermal Therapy with Accelerated Hepatobiliary Excretion - Sihang Zhang; Sheng Yu; Jingwen Sun; Teng Huang; Hongzheng Lin; Zhe Li; Zeyu Xiao; Wei Lu (Pharmaceutics, 2024)
Gold-based nanoparticles for surface-enhanced Raman scattering (SERS) imaging show great potential for precise tumor detection and photothermal therapy (PTT). However, the metabolizability of gold nanoparticles (Au NPs) raises big concerns. Herein, we designed a core-shelled nanostructure of copper sulfide (CuS)-coated Au NPs with surface pegylation (PEG-Au@CuS NSs). The excreted Au in the gallbladders at 1 h and 4 h in mice injected with PEG-Au@CuS NSs was 8.2- and 19.1-fold of that with the pegylated Au NPs (PEG-AuNPs) of the same Au particle size, respectively. By loading the Raman reporter 3,3′-Diethylthiatricarbocyanine iodide (DTTC) in the core–shell junction of PEG-Au@CuS NSs, the PEG-Au-DTTC@CuS NSs exhibited the Raman signal-to-noise (S/N) ratio of 4.01 after 24 h of intravenous (IV) injection in the mice bearing an orthotopic CT26-Luc colon tumor. By contrast, the DTTC-coated PEG-AuNPs (PEG-Au-DTTC NPs) achieved an S/N ratio of 2.71. Moreover, PEG-Au-DTTC@CuS NSs exhibited an increased photothermal conversion effect compared with PEG-Au-DTTC NPs excited with an 808-nm laser. PEG-Au-DTTC@CuS NSs enabled intraoperative SERS image-guided photothermal therapy for a complete cure of the colon tumor-bearing mice. Our data demonstrated that the PEG-Au-DTTC@CuS NSs are promising intraoperative Raman image-guided theranostic nanoplatform with enhanced hepatobiliary excretion.